O laboratório de educação matemática na formação continuada do professor de matemática - Costa, Jaqueline Gomides da (2014)
This study is the result of an investigation about the process of continuing education experienced by a teacher of Primary Education, of a public school in the state of Goiânia - GO, in the context of a pedagogical practice supported by the use of teaching resources belonging to a Mathematics Education laboratory. In the constitution of this research, we carry out an analysis of the process of reflection of the teachers own pedagogical practice and a review of the possible benefits of the use of elaborated and developed activities with the aid of the laboratory practice of the collaborative teacher and student learning resources. For this, we adopted theoretical framework authors dealing with themes such as, laboratory mathematics education, teachers training in math, and critical reflection on teaching practice. In this context, we adopt the approach of qualitative research in the form of participatory research, in order to analyze the educational practice of teachers of basic education, using as instruments for collecting data through participant observation, field diary, filming, the questionnaire and the semi-structured interview. In this perspective, the analysis of the data led us to observe the development of this work process in three categories: From naive curiosity to epistemological curiosity; development amid transformative practices; and the meaning of the experience for the teacher and students. The analysis of these data indicates a change in the practice of this teacher, including in relation to their attitude towards class.